Traditional Market Mechanism On Increasing Income In Sharia Economic Perspective (Study Of Doro Market, Pekalongan Regency) - Aljanatun Vivin; Hendri Hermawan Adinugraha (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2022)
Economics is a study of a fixed way or method for allocating natural resources and human resources, with the aim of achieving optimization and achieving the best goals. Regulations in the production and distribution of goods are entrusted to self-regulating mechanisms, including services, at a certain price based on that price will meet demand. Trade arises from the effort to find goods on the outer boundaries of the territory. If a human community never does external trade at all, then there is no need for a market to emerge. The research method used in this study is a qualitative method. The qualitative method is to find out or describe the reality of the events studied. Making it easier for the author to obtain objective data in order to know the Traditional Market Mechanisms Against Income Increase in the Sharia Economic Perspective (Case Study of Doro Market, Pekalongan Regency). Qualitative research method is a research method used to examine the condition of a natural object (as opposed to an experiment) where the researcher is the key instrument. That means that qualitative research is a plan and method that researchers will use to examine the condition of natural objects (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combined), data analysis is inductive/qualitative, and the results of qualitative research emphasize meaning rather than generalizations.